Dynamics of Capillaria-hepatica-induced hepatic septal fibrosis in rats - Gaban,Lidiane (2010)
INTRODUCTION: The pathogenesis of septal hepatic fibrosis, induced in rats by Capillaria hepatica infection, was studied with the aid of a large collection of stored paraffin blocks, representative of the different evolutive phases of fibrosis which appeared in 100% of infected rats. METHODS: Studies were conducted involving histology, immunohistochemistry, immunofluorescence and morphometric methods, in order to observe the dynamic behavior of the cellular and matrix components of fibrosis, over a one year period of evolution. RESULTS: Observation verified that septal fibrosis originates from several portal spaces simultaneously. Its origin and progression involve blood vessel proliferation (angiogenesis), multiplication of actin-positive cells (pericytes and myofibroblasts) and progressive collagen deposition. By the end of 4-5 months, a progressive decrease in all these components was observed, when signs of regression of septal fibrosis became more evident over time. CONCLUSIONS: Besides indicating the fundamental role played by angiogenesis in the pathogenesis of fibrosis, these morphological data concerning the dynamics of this C. hepatica experimental model proved to be adequate for future investigations regarding the functional aspects of fibrosis induction, progression and regression.